Genetic Divergence of Austroasiatic Speaking Groups in the Northeast of Thailand: A Case Study on Northern Khmer and Kuy - Panthipa Chantakot (Science Faculty of Chiang Mai University, 2019)
The Austroasiatic speaking people are regarded as the native inhabitants in Thailand, predating the coming of Kra-Dai-speaking groups from Southwestern China. Two of the largest Austroasiatic speaking groups in Northeastern Thailand are the Northern Khmer and the Kuy. Previous genetic surveys of these two ethnic groups mostly used mitochondrial DNA polymorphisms, therefore, the present study intended to utilize the variability of autosomal microsatellites to deeply investigate the genetic structure of the Northern Khmer and the Kuy. Thirty-one and forty-seven samples of unrelated Northern Khmer and Kuy, respectively, were genotyped for 15 microsatellites. Distance based and model based clustering methods were employed to elucidate the evolutionary relationship between the studied populations and ten other linguistically and geographically diverse comparable populations in Thailand. Analysis of Molecular Variance and Factorial Correspondence Analysis revealed a genetic heterogeneity in Austroasiatic populations but an opposite trend was observed in the genetically homogeneous Kra-Dai populations. STRUCTURE result shows that the Northern Khmer contributes approximately 31% of their genes to the gene pool of their neighbor, Lao Isan, indicating a genetic exchange among them. The extreme genetic divergence of the Kuy from other populations seems to be much higher than the Northern Khmer. A genetic admixture of the Northern Khmer and with their neighboring Lao Isan was detected and this is consistent with archaeological evidence.